2014
DOI: 10.1111/jace.12875
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Partial Discharge and Fracture Strength in Piezoelectric Ceramics

Abstract: Although piezoelectric ceramics are widely used, the structural reliability of these materials in long‐term service is still a concern. In this study, a nondestructive method for assessing material strength reliability using partial discharge (PD) tests is proposed. The PD inception electric field and the flexure strength are both controlled by the defects in the ceramics which suggests that the PD test can be an alternative nondestructive method for evaluating the structural reliability of piezoelectric ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The construction of a prototype is proposed to obtain the following patterns of partial discharges: (1) internal PD, (2) superficial PD, (3) corona discharge in air, and (4) corona discharge in oil, additionally considering two new PD patterns: (1) false contact and (2) floating ground. The validation of the proposed prototype was performed using the statistical method and the norm IEC 60270 can know insulation degradation unlike acoustic measurements which allow knowing only the location of the PD in tests in the laboratory [12][13][14][15].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The construction of a prototype is proposed to obtain the following patterns of partial discharges: (1) internal PD, (2) superficial PD, (3) corona discharge in air, and (4) corona discharge in oil, additionally considering two new PD patterns: (1) false contact and (2) floating ground. The validation of the proposed prototype was performed using the statistical method and the norm IEC 60270 can know insulation degradation unlike acoustic measurements which allow knowing only the location of the PD in tests in the laboratory [12][13][14][15].…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…In this scheme, C a represents the test object, C b is a blocking capacitor, Z mi is a quadripole measuring impedance. Details of the PD system set-up can be found in our previous study [10]. This PD measuring system has a resolution of 1 pC.…”
Section: Electrical Partial Discharge Testmentioning
confidence: 99%
“…For a lead zirconate titanate (PZT) ceramic with an indentation crack, the electric field enhancement in the region of a crack tip was evidenced by measuring the electrical potential distribution using Kelvin probe microscopy [9]. In our previous work, we have also shown that the PD inception field for a soft PZT ceramic is as low as 1 kV/mm [10]. Furthermore, it should also be noted that repetitive PDs may cause progressive long-term deterioration of the piezoelectric system when the operating voltage is higher than the PD inception voltage, although a single PD magnitude is small.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that repetitive PDs in insulating materials can result in long-term damages since the released energy can cause a rapid heating and ultimately dielectric breakdown [21][22][23][24]. Measurements of PDs are commonly used in electrical engineering to assess the degradation and aging of high-voltage insulators [25][26][27][28][29], but the method has not yet been broadly adopted for ceramic materials [30][31][32][33][34]. In the context of flash sintering, PD measurements were recently shown to be an efficient method to characterize the quality and number of the electrode/sample contact areas when no Pt paste was used to sinter Y-stabilised zirconia (YSZ) above 250 • C [35].…”
Section: Introductionmentioning
confidence: 99%